Pengaruh Model Pembelajaran Problem Based Learning Terhadap Kemampuan Berpikir Kritis dan Self Confidence Peserta Didik: The Influence of the Problem-Based Learning Model on Students Critical Thinking Skills and Self-Confidence - Agustin, Della Hasna; Hermawan, Yoni; Solihat, Ai Nur (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
This research was prompted by the low critical thinking skills and self-confidence observed among students at SMAN 6 Tasikmalaya. The study aimed to determine the effect of the Problem-Based Learning (PBL) model on students' critical thinking skills and self-confidence in the economics subject, specifically on the concept of international trade. This study employed a quasi-experimental method with a post-test-only control group design. Data were collected through essay tests and questionnaires. The population for this research consisted of all 198 eleventh-grade social science (XI IPS) students at SMAN 6 Tasikmalaya during the 2023/2024 academic year. The sample included 39 students from class XI IPS 4 as the experimental group and 39 students from class XI IPS 5 as the control group, selected using a purposive sampling technique. The results of the study conclude that the Problem-Based Learning model has a significant influence on students' critical thinking skills and self-confidence.